Evaluating the cost utility of racecadotril for the treatment of acute watery diarrhea in children: the RAWD model - Rautenberg TA; Zerwes U; Foerster D; Aultman R (Dove Medical Press, 2012)
Tamlyn Anne Rautenberg1,2, Ute Zerwes1, Douglas Foerster3,4, Rick Aultman51Assessment in Medicine GmbH, Lörrach, Germany; 2Leeds Institute of Health Sciences, University of Leeds, Leeds, United Kingdom; 3Abbott Products Operations AG, Allschwil, Switzerland; 4University of Bielefeld, School of Public Health, Bielefeld, Germany; 5Semalytics, Arizona, United States of AmericaBackground: The safety and efficacy of racecadotril to treat acute watery diarrhea (AWD) in children is well established, however its cost effectiveness for infants and children in Europe has not yet been determined.Objective: To evaluate the cost utility of racecadotril adjuvant with oral rehydration solution (ORS) compared to ORS alone for the treatment of AWD in children younger than 5 years old. The analysis is performed from a United Kingdom National Health Service (NHS) perspective.Methods: A decision tree model has been developed in Microsoft® Excel. The model is populated with the best available evidence. Deterministic and probabilistic sensitivity analyses (PSA) have been performed. Health effects are measured as quality-adjusted life years (QALYs) and the model output is cost (2011 GBP) per QALY. The uncertainty in the primary outcome is explored by probabilistic analysis using 1000 iterations of a Monte Carlo simulation.Results: Deterministic analysis results in a total incremental cost of –£379 in favor of racecadotril and a total incremental QALY gain in favor of racecadotril of +0.0008. The observed cost savings with racecadotril arise from the reduction in primary care reconsultation and secondary referral. The difference in QALYs is largely attributable to the timely resolution of symptoms in the racecadotril arm. Racecadotril remains dominant when base case parameters are varied. Monte Carlo simulation and PSA confirm that racecadotril is the dominant treatment strategy and is almost certainly cost effective, under the central assumptions of the model, at a commonly used willingness to pay proxy threshold range of £20,000–£30,000 per QALY.Conclusion: Racecadotril as adjuvant therapy is more effective and less costly compared to ORS alone, from a UK payer perspective, for the treatment of children with acute diarrhea.Keywords: cost effectiveness, health economic model, infant, QALY, racecadotril, acute watery diarrhea